Tinjauan Literatur : Determinan Stunting Pada 1000 Hari Pertama Kehidupan Anak - Yudhistirana; Mona Nulanda; Maya Susanti (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Stunting is a growth disorder in children characterized by height-for-age below the standard due to prolonged nutritional deficiency. This condition affects physical development, learning ability, and metabolic health, and it tends to be persistent. In Indonesia, the prevalence of stunting remains high. This study was conducted to identify the causes of stunting during the first 1,000 days of life. The method used was a literature review with a narrative review approach. The results show that risk factors for stunting include prenatal conditions such as low birth weight, maternal nutritional status during pregnancy, and maternal height. In addition, low maternal education, limited access to healthcare services, lack of exclusive breastfeeding, infections, and poor dietary patterns also contribute. Strategies proven effective according to the literature include early nutrition education, nutritional supplementation, and technology-based growth monitoring. The most consistently identified determinant is low birth weight (LBW).